2021
DOI: 10.1038/s41598-020-80653-y
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of oral bacteria to the fetus during late gestation

Abstract: The fetus develops in a privileged environment, as the placenta serves as both a gateway for nutrients and a barrier for pathogen transfer to the fetus. Regardless, recent evidence suggests the presence of bacterial DNA in both placenta and fetus, and we have reported that DNA and protein from small numbers of bacteria gain access to the fetus from the maternal bloodstream. Other routes of environmental bacterial transfer from the mother to fetus remain unknown, as well as the physiological relevance of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 70 publications
0
6
0
1
Order By: Relevance
“…We did not test the specific hypothesis that the oral microbiome can be transferred to the pregnancy in our study. The recent demonstration that fluorescently-labeled bacteria that are administered orally, intravenously, or vaginally will populate the ovine fetus during late pregnancy ( Yu et al, 2021 ) clearly demonstrates that exposure of the dam to bacteria through an oral or other route can affect the microbiome of the pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…We did not test the specific hypothesis that the oral microbiome can be transferred to the pregnancy in our study. The recent demonstration that fluorescently-labeled bacteria that are administered orally, intravenously, or vaginally will populate the ovine fetus during late pregnancy ( Yu et al, 2021 ) clearly demonstrates that exposure of the dam to bacteria through an oral or other route can affect the microbiome of the pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…A select group of microorganisms, including Aggregatibacter , Campylobacter , Capnocytophaga , Eikenella , Escherichia coli , F. nucleatum , Gemella , Leptotrichia , Neisseria , Peptostreptococcus , Streptococcus , and Veillonella , were detected in the mouse placentas, demonstrating that multiple oral species are capable of oral‐utero translocation 26 . In addition, a recent study found oral Staphylococcus aureus transmitting to fetal sheep brain stimulating changes in gene expression 27 . Detailed mechanistic studies focus mainly on F. nucleatum and Porphyromonas gingivalis (Table 2).…”
Section: Mechanistic Link Between Periodontal Disease and Adverse Pre...mentioning
confidence: 98%
“…20,21,24,25 26 In addition, a recent study found oral Staphylococcus aureus transmitting to fetal sheep brain stimulating changes in gene expression. 27 Detailed mechanistic studies focus mainly on F. nucleatum and Porphyromonas gingivalis (Table 2).…”
Section: Direct Pathwaysmentioning
confidence: 99%
“…A few studies suggest that the maternal gut, vagina, and oral cavity could potentially serve as sources for seeding the foetal microbiome via the placenta during pregnancy (Aagaard et al 2014 , Gomez-Arango et al 2017 , Wang et al 2021a , Hummel et al 2022 , Xiao and Zhao 2023 ). A study in sheep, investigating the routes through which nonpathogenic bacteria can enter the foetus, was unable to recover live bacteria from foetal tissue (Yu et al 2021 ). However, the same study showed that DNA and proteins derived from bacteria introduced into the maternal mouth could be detected in the foetal brain and trigger alterations in foetal gene expression, representing an intriguing avenue of communication between the foetus and its mother’s environment, and a potential mechanism to ready the foetus for ex-utero life.…”
Section: Microbial Recruitment At the Interfacesmentioning
confidence: 99%